1997
DOI: 10.1590/s0036-46651997000300008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in Brazil: report of a national survey (Florianópolis, SC, 1995)

Abstract: In order to investigate epidemiological aspects of hepatocellular carcinoma (HCC) in Brazil, basic informations about cases diagnosed from January 1992 to December 1994 were requested to several medical centers of different Brazilian States. A simple questionnaire included age, sex, alcohol abuse (over 80g/day), associated liver cirrhosis, persistent HBV infection (HBsAg), HCV infection (anti-HCV) and serum levels of alpha fetoprotein. 287 cases, over 16 years old, from 19 medical centers of 8 States (Pará, Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 0 publications
4
43
0
13
Order By: Relevance
“…This finding was probably due to the fact that the collection was carried out in an ambulatory, where more stable patients are evaluated. The fact that group HCC is composed by younger patients is in accordance with the literature, as is the predominance of male patients in both groups (12) .…”
Section: Discussionsupporting
confidence: 89%
“…This finding was probably due to the fact that the collection was carried out in an ambulatory, where more stable patients are evaluated. The fact that group HCC is composed by younger patients is in accordance with the literature, as is the predominance of male patients in both groups (12) .…”
Section: Discussionsupporting
confidence: 89%
“…The results of the fi rst survey indicated that HBV was a common factor associated with HCC in the North and Northeast regions, whereas HCV was the main risk factor overall, especially in metropolitan areas in the South and Southeast regions 9 . The second survey yielded different results: HCV was found to be the main associated risk factor in all regions, but a high frequency of HBV-associated cases in the North, Central West and Northeast regions was also noted 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a series of HCC cases that were diagnosed in Belo Horizonte, MG, the main associated factor was found to be HCV (44% of cases), while HBV infection was observed in 23.5% of cases 12 . Associated liver cirrhosis has been reported at different frequencies in HCC cases in Brazil, ranging from 87% in the fi rst national survey 9 to 98% in the second survey 10,11 . Because Brazil is a large country and the environmental risk factors for HCC may vary across regions, we chose to examine the main associated risk factors in 274 cases of hepatocellular carcinoma diagnosed at the University Hospital in Vitória; we thus investigated HBV and HCV infections and chronic alcoholism in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, its clinical and epidemiological aspects widely vary amongst different regions 4 , where is considered a neoplasm of low prevalence in general 5 .…”
Section: Introductionmentioning
confidence: 99%